Customer Participation, e-Service Quality, Satisfaction: (e)Service Dominant Logic Trinity. Issue 3 (16th April 2019) - Fotiadis, Thomas
Abstract: This study aims to assess the effects of customer participation behavior on perceived e-service quality and satisfaction in Greek e-shops, by analyzing data collected by 335 Greek customers, employing Explanatory and Confirmatory Factor Analysis (SEM) of the ADF method. The research explores and expands existing literature, focusing on self-service technologies and specifically on e-shopping, while customer participation is considered a multi-dimensional construct. The results reveal that one dimension of customer participation behavior (responsible behavior) positively affects perceived service quality, as well as customer satisfaction, while information seeking affects only e-service quality, whereas the two dependent variables are not affected by information sharing.